ANALISIS KOMPARATIF PENDAPATAN USAHATANI JAGUNG MANIS DAN JAGUNG HIBRIDA DI UNIT PEMUKIMAN TRANSMIGRASI (UPT) BULUPOUNTU JAYA KECAMATAN SIGI BIROMARU KABUPATEN SIGI - Haryanto Lenak; Jonh Tomy; Nurmedika Nurmedika (AGROTEKBIS : JURNAL ILMU PERTANIAN (e-journal), 2022)
The aim of this study was to investigate and compare the earnings of cultivating sweet corn and hybrid corn. The research was carried out at the Transmigration Settlement Unit of Bulupountu Jaya, located in the Sigi Biromaru sub district of Sigi district, between March and May 2021. The participants in the study were chosen using Proportional Stratified Random Sampling, with 25 sweet corn farmers and seven hybrid corn farmers selected as the samples using the Slovin formula from a total of 32 people. Income (π) and comparative analysis, along with t-tests, were used to analyze the data. The findings revealed that the average income per hectare from sweet corn farming in one planting season at UPT Bulupountu Jaya was IDR 6,511,985.22, while at the hybrid corn farming was IDR 4,165,539.90. The results of the t-test demonstrated that the income of sweet corn and hybrid corn farmers in UPT Bulupountu Jaya differed significantly, with a t-value of 2.201>2.042 (α0.25%). Thus, the null hypothesis (H0) was rejected, and the alternative hypothesis (H1) was accepted.